Superb microvascular imaging Doppler technique in the evaluation of ovarian stromal vascularity in women with polycystic ovary syndrome - Irem Senyuva; Cigdem Ozturk Turan; Gokce Yildirim Yuksel; Senem Senturk (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the assessment of intra-ovarian stromal vascularity through transabdominal ultrasonography with colour Doppler imaging, power Doppler imaging, colour superb microvascular imaging and monochrome superb microvascular imaging in polycystic ovary syndrome cases. Method: The retrospective cross-sectional study was conducted at the Obstetrics and Gynaecology outpatient department of the Usak Training and Research Hospital, Turkey, from April 11 to June 18, 2018, and comprised grayscale colour Doppler imaging, power Doppler imaging, colour superb microvascular imaging and monochrome superb microvascular imaging of women with polycystic ovary syndrome. The recorded video images were evaluated by three radiologists and rated through consensus decision. Mean values for age, body mass index, follicle stimulating hormone and l uteinizing hormone levels, luteinizing hormone-follicle stimulating hormone ratio, Ferriman Gallwey score, and mean ovarian volume of the subjects were evaluated. Data was analysed using Number Cruncher Statistical System. Results: Of the 54 women evaluated, data of 42(77.8%) was included. There were a total of 83 ovaries, as the left ovary of 1(1.2%) patient was not visible. The mean age and body mass index were 24.02±5.8 years and 25.08±4.5kg/m2. Mean follicle stimulating hormone and luteinizing hormone levels were 5.51±1.91 and 7.91±6.13m IU/mL. Luteinizing hormone/follicle stimulating hormone ratio and Ferriman Gallwey score were 1.4±0.8 and 8.67 ±6.94, respectively. The mean ovarian volume was 12.2±3.43 cm3. The detection of vascularity was colour Doppler imaging 0.72±0.97, power Doppler imaging 0.96±1.08, colour superb microvascular imaging 2.47±1.25, and monochrome superb microvascular imaging 2.75±1.31. The techniques were significant for superb microvascular imaging Doppler than conventional Doppler (p<0.001). Hyper-ovarian stromal vascularity, like a 'stellate' sign, was detected in 17(20.5%) of the total 83 ovaries analysed. Conclusions: Transabdominal ultrasonography-colour superb microvascular imaging was found to be more effective in detecting ovarian vascularity than conventional Doppler technique in women with polycystic ovary syndrome. Key Words: Microvessels, Polycystic ovary syndrome, Ultrasonography, Doppler.